LEGAL SECURITY OF OWNERSHIP OF LAND CERTIFICATES POST EXCHANGING FOREST AREA FOR RESIDENTS RELOCATION IN NGROTO DUSUN, WONOGIRI, CENTRAL JAVA - Yusse Putri Ganadi; Nunik Nurhayati; Rizka Rizka; Moh Indra Bangsawan; Michel Lee Tranh (Faculty of Law, Khairun University, 2023)
This study aims to discuss the description of the implementation process of exchanging forest areas for the relocation of residents and legal certainty of ownership of community land certificates after the relocation of community forest area exchanges in Dusun Ngroto. The research method used in this research is juridical-empirical descriptive by using qualitative data analysis methods to review literature and events that actually occurred through observation and interviews. The research location is in Ngroto Hamlet, Pare Village, Selogiri District, Wonogiri Regency. The results of the discussion found that 1 )The background to the relocation was due to the fact that in March 1999 in the Ngroto Hamlet area a landslide occurred resulting in as many as 43 family cards (115 people), supporting factors for relocation including social relations, economy, community involvement and participation with the government while the inhibiting factors are infrastructure, policies that underlie relocation based on humanitarian considerations. 2) Legal certainty of ownership of land certificates after the relocation residents have not obtained the rights to the land they occupy regarding evidence of land certificates, the Wonogiri Regency Government is in the process of eliminating the land ownership rights of residents who have been victims of the landslide disaster 11.66 Ha (Eleven and Sixty Six One Hundred Hectares) with a replacement land obligation of 13.11 Ha (Thirte